Radially and temporally resolved electric field of positive streamers in air and modelling of the induced plasma chemistry. (8th July 2016) - Hoder, T; Šimek, M; Bonaventura, Z; Prukner, V; Gordillo-Vázquez, F J
Abstract: The initial stages of transient luminous events (TLEs) occurring in the upper atmosphere of the Earth are, in a certain pressure range, controlled by the streamer mechanism. This paper presents the results of the first laboratory experiments to study the TLE streamer phenomena under conditions close to those of the upper atmosphere. Spectrally and highly spatiotemporally resolved emissions originating from radiative states N 2 ( C 3 Π u ) (second positive system) and N 2 + ( B 2 Σ u + ) (first negative system) have been recorded from the positive streamer discharge. Periodic ionizing events were generated in a barrier discharge arrangement at a pressure of 4 torr of synthetic air, i.e. simulating the pressure conditions at altitudes of ≃37 km. Employing Abel inversion on the radially scanned streamer emission and a 2D fitting procedure, access was obtained to the local spectral signatures within the over 10 6   m s −1 fast propagating streamers. The reduced electric field strength distribution within the streamer head was determined from the ratio of the N 2 + / N 2 band intensities with peak values up to 500 Td and overall duration of about 10 ns. The 2D profiles of the streamer head electric fields were used as an experimentally obtained input for kinetic simulations of the streamer-induced air plasma chemistry. The radial and temporal computed distribution of the ground vibrational levels of the radiative states involved in the radiative transitions analyzed (337.1 nm and 391.5 nm), atomic oxygen, nitrogen, nitric oxide and ozone concentrations are vizualized and discussed in comparison with available models of the streamer phase of Blue Jet discharges in the stratosphere.